(untitled) (Islas, 2020)
El presente trabajo rescata los elementos más significativos que al cabo de treinta años sobreviven en la memoria de un musicólogo y profesor universitario ecuatoriano, que visitó Cuba en 1990 por motivos culturales oficiales; cuyo paso por La Habana y Santa Clara le permitió conformar todo un imaginario articulado por la clave de la fascinación. Es un tributo del autor al número especial que la revista Islas dedica a la cultura de Ecuador; y posee notable interés antropológico. The present work rescues the most significant elements that after thirty years survive in the memory of an Ecuadorian musicologist and university professor, who visited Cuba in 1990 for official cultural reasons; whose passage through Havana and Santa Clara allowed him to form an entire imaginary articulated by the key to fascination. It is a tribute of the author to the special issue that the magazine Islas dedicates to the culture of Ecuador; and has remarkable anthropological interest.